Role of selected adipokines in psoriasis - Baran, Anna; Flisiak, Iwona; Chodynicka, Bożena (Dermatology Review/Przegląd Dermatologiczny, 2011)
Psoriasis is a chronic and recurrent skin disease, affecting 1.5-3% of the population. It is characterized by abnormal epidermal proliferation, immunological disturbances with predominance of Th1 response and complex pathogenesis. There are correlations between psoriasis and obesity, cardiovascular diseases, diabetes and metabolic syndrome. Adipokines, bioactive substances secreted by adipose tissue, exert a variety of metabolic activities and are associated with many diseases. In the article the possible role of adipokines in psoriasis is evaluated.